Communication skills (CS) training of physicians in China and its role in actual challenges of patient-physician relationship: a cross-sectional survey - Du, Junfeng; Mayer, Gwendolyn; Posenato, Elisabetta; Hummel, Svenja; Zafar, Ali; Bärnighausen, Till; Schultz, Jobst-Hendrik (BMC medical education, 2022)
The Chinese healthcare system is affected by frequent disputes between physicians and patients. Although recent reforms have contributed towards improving the patient-physician relationship, distrust in physicians is still high. Communication skills (CS) training of physicians holds the key to improving patient confidence and diffusing stressful situations. This survey reports on the status of CS training in medical education in China, and the experiences and attitudes of physicians towards CS training.